Clinicopathological Features of Cutaneous Findings of SARS-CoV-2 Infection - Bengu COBANOGLU; Filiz CEBECI; Mustafa SIMSEK; Seyma OZKANLI (Medeniyet Medical Journal)
Objective: In December 2019, severe acute respiratory syndrome coronavirus-2, which emerged in Wuhan, China, spread rapidly and created a pandemic. Coronavirus disease-2019 (COVID-19) can affect different organ systems, including the skin. Recently, COVID-19 cases with skin lesions of different clinicopathological features have been published. This study aimed to present the histopathological features of 19 COVID-19 cases with cutaneous findings and discuss them in light of the literature. Methods: Skin biopsy specimens of 19 patients with skin rashes associated with COVID-19 were evaluated histopathologically and clinically. Results: Clinical manifestations of rashes developed in eight female, seven male, and four pediatric patients with COVID-19. Urticaria/urticarial vasculitis (n=7), maculopapular eruption (n=7), panniculitis (n=2), purpuric eruptions (n=2), and livedoid-like lesions were noted. Histopathologically, besides the inflammatory findings, the most striking feature was that the vessels were more or less affected in almost all cases. Conclusions: Cutaneous lesions associated with COVID-19 are increasingly being reported. We believe that every data presented about this disease, which has many unknowns, will shed light on future research. Every case can lead us a new way.